HOW PERSONALITY SHAPES STUDENT MOTIVATION: A REVIEW OF KEY FINDINGS - Stefhani, Stefhani; Arbi, Arbi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2025)
This article explores the relationship between personality and student learning motivation through a literature review approach, also known as library research. This method involves reading, analyzing, and comparing various literature sources, including research reports, academic journals, papers, books, and other relevant references, without requiring fieldwork. The study discusses several key aspects: the concept of personality; factors determining personality; personality patterns; the concept of learning motivation; factors influencing learning motivation; the objectives of providing motivation; indicators of student learning motivation; and the relationship between personality and student learning motivation. The findings of this study provide insights for educators, policymakers, and researchers into the importance of understanding personality traits to enhance students' learning motivation. By tailoring teaching strategies to align with different personality patterns, educators can foster a more engaging and supportive learning environment. Furthermore, the study highlights the need for educational interventions that address both personality development and motivational factors, thereby contributing to the overall improvement of student academic performance and personal growth.